Role of drug catabolism, modulation of oncogenic signaling and tumor microenvironment in microbe-mediated pancreatic cancer chemoresistance. (September 2022) - Capula, Mjriam; Perán, Macarena; Xu, Geng; Donati, Valentina; Yee, Dicky; Gregori, Alessandro; Assaraf, Yehuda G.; Giovannetti, Elisa; Deng, Dongmei
Abstract: Pancreatic ductal adenocarcinoma (PDAC) has one of the highest incidence/death ratios among all neoplasms due to its late diagnosis and dominant chemoresistance. Most PDAC patients present with an advanced disease characterized by a multifactorial, inherent and acquired resistance to current anticancer treatments. This remarkable chemoresistance has been ascribed to several PDAC features including the genetic landscape, metabolic alterations, and a heterogeneous tumor microenvironment that is characterized by dense fibrosis, and a cellular contexture including functionally distinct subclasses of cancer-associated fibroblasts, immune suppressive cells, but also a number of bacteria, shaping a specific tumor microbiome microenvironment. Thus, recent studies prompted the emergence of a new research avenue, by describing the role of the microbiome in gemcitabine resistance, while next-generation-sequencing analyses identified a specific microbiome in different tumors, including PDAC. Functionally, the contribution of these microbes to PDAC chemoresistance is only beginning to be explored. Here we provide an overview of the studies demonstrating that bacteria have the capacity to metabolically transform and hence inactivate anticancer drugs, as exemplified by the inhibition of the efficacy of 10 out of 30 chemotherapeutics by Escherichia coli . Moreover, a number of bacteria modulate specific oncogenic pathways, such as Fusobacterium nucleatum, affecting autophagy and apoptosis induction by 5-fluorouracil and oxaliplatin. We hypothesize that improved understanding of how chemoresistance is driven by bacteria could enhance the efficacy of current treatments, and discuss the potential of microbiome modulation and targeted therapeutic approaches as well as the need for more reliable models and biomarkers to translate the findings of preclinical/translational research to the clinical setting, and ultimately overcome PDAC chemoresistance, hence improving clinical outcome.